Impact of cognitive intervention on cognitive symptoms and quality of life in idiopathic Parkinson’s disease: a randomized and controlled study - Sousa,Nariana Mattos Figueiredo (2021)
ABSTRACT. Pharmacological treatments for mild cognitive impairment (MCI), are lacking, and alternative approaches have been implemented, including cognitive training (CT). Objective: To determine the impact of CT on cognitive and quality of life measures in patients with Parkinson’s disease (PD) who were seen a hospital neurorehabilitation program. Methods: Thirty-nine individuals with MCI-PD, according to the Movement Disorder Society, were randomly distributed into two groups: experimental and control group, matched for demographic and clinical characteristics. Both groups were assessed for cognition and quality of life at the beginning of the study and at the end of the intervention protocol. The following instruments were used to assess cognition and quality of life: Addenbrooke’s Cognitive Examination III, Digit Span, Trail Making Test (TMT, A and B) and Parkinson disease quality of life questionnaire. The experimental group (EG) engaged in CT, whereas the control group (CG) underwent activities of the general rehabilitation program. Results: No baseline evaluation differences were found. Intergroup analysis showed differences in measures, such as total score (1.977, p=0.0480) and visuospatial domain (-2.636, p=0.0084) of the ACE-III, with the EG performing better, in addition to better performance in TMT-B mistakes (-1.928, p=0.0439). Intragroup analysis revealed that the EG showed significant improvement in almost all the cognitive variables, well as in self-reported quality of life (total score and mobility, activities of daily living, body discomfort dimensions). Conclusions: Engagement in cognitive activities was associated with better cognitive abilities in PD-MCI. Future studies should consider the long-term effect of this type of intervention and impact on functional activities.